2007
DOI: 10.1183/09031936.00043306
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and metabolic effects of CPAP in obese males with OSA

Abstract: Obstructive sleep apnoea is associated with increased blood pressure and other features of the metabolic syndrome. The aim of the present study was to determine the relative effectiveness of continuous positive airway pressure (CPAP) in modifying these outcomes.A randomised placebo-controlled blinded crossover trial comparing cardiovascular and metabolic outcomes after 6 weeks of therapeutic and sham CPAP was performed in 34 CPAPnaïve patients (mean¡SD body mass and respiratory disturbance indices were 36.1¡7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
221
1
15

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(253 citation statements)
references
References 41 publications
(48 reference statements)
16
221
1
15
Order By: Relevance
“…Our study was primarily focused on changes in BC. We thus did not record changes in other clinically important measures such as blood pressure, which has been shown to decrease in several trials (69)(70)(71). Finally, using a prepost design, we were able to detect changes within specific age categories only.…”
Section: Discussionmentioning
confidence: 96%
“…Our study was primarily focused on changes in BC. We thus did not record changes in other clinically important measures such as blood pressure, which has been shown to decrease in several trials (69)(70)(71). Finally, using a prepost design, we were able to detect changes within specific age categories only.…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that by an association with the metabolic changes hs-CRP was related to HRR-1 in the present study. However, in an uncontrolled study we had also shown that in patients with severe OSA, HRR is improved by CPAP [11], while recent studies on the effects of CPAP on hs-CRP and insulin resistance have been neutral [12,13]. Thus, the relationship between HRR-1 and hs-CRP seems to be more complicated and remains to be elucidated.…”
mentioning
confidence: 91%
“…An interventional study by Coughlin et al [40] found no significant change in weight, body fat, insulin resistance or lipid profiles with CPAP treatment as opposed to sham CPAP therapy. Nevertheless, there were improvements in blood pressure control following CPAP intervention.…”
Section: Metabolic Syndromementioning
confidence: 99%